Knowns and unknowns in the care of pediatric familial hypercholesterolemia - Martin, Andrew C. (J Lipid Res, 2017)
Familial hypercholesterolemia (FH) is a common genetic disorder that causes elevated LDL cholesterol levels from birth. Untreated FH accelerates atherosclerosis and predisposes individuals to premature coronary artery disease (CAD) in adulthood. Mendelian randomization studies have demonstrated that LDL cholesterol has both a causal and cumulative effect on the risk of CAD. This supports clinical recommendations that children with FH commence pharmacological treatment from the age of 8 to 10 years, to reduce the burden of hypercholesterolemia. Worldwide, the majority of children with FH remain undiagnosed. Recent evidence suggests that the frequency of FH is at least 1 in 250 and this constitutes a public health issue. We review and identify the knowns and unknowns concerning the detection and management of pediatric FH that impact on the developing model of care for this condition.